Cancer-associated myasthenic (Eaton-Lambert) syndrome: distribution of abnormality and effect of treatment. Issue 8 (August 1984) - Ingram, D A; Davis, G R; Schwartz, M S; Traub, M; Newland, A C; Swash, M
Abstract : Treatment with plasma exchange, steroids, immunosuppressant drugs and cytotoxic chemotherapy was effective in two cases of cancer-associated Eaton-Lambert myasthenic syndrome. The clinical improvement noted during treatment was accompanied by improvement in the electrophysiological abnormality; this was much more marked in abductor digiti minimi and trapezius than in extensor digitorum brevis.